PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PERBANKAN DI BEI PERIODE 2013-2015 - Susanti Susanti (Jurnal Bisnis Darmajaya, 2016)
Intellectual capital is the result of three main elements of an organization (human capital, structural capital, and customer capital) as science and technology manifestation which can provide more positive value for companies in the form of competitive advantages of the organization. The objective of this study was empirically to demonstrate the effect of the intellectual capital on the banking value. Independent variables in this study were the intellectual capital and a dependent variable was the banking value which provided by Tobin's Q, PBV and PER. Population of this study was the 43 banks banking companies listed on the Indonesia Stock Exchange in 2013 to 2015. Sample collecting method used in this study was a purposive sampling method. Data analysis technique used in this study was PLS (Partial Least Square). The result of this study showed that the intellectual capital had no significant effect on banking value.Keywords: Intellectual Capital, Banking Value, and PLS.